2017
DOI: 10.1016/j.brainres.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical differences between target-specific populations of rat dorsal raphe projection neurons

Abstract: Serotonin (5-HT)-containing neurons in the dorsal raphe (DR) nucleus project throughout the forebrain and are implicated in many physiological processes and neuropsychiatric disorders. Diversity among these neurons has been characterized in terms of their neurochemistry and anatomical organization, but a clear sense of whether these attributes align with specific brain functions or terminal fields is lacking. DR 5-HT neurons can co-express additional neuroactive substances, increasing the potential for individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 87 publications
5
16
0
Order By: Relevance
“…Our retrograde tracing from eight diverse target sites, combined with image registration to compare the data in the same reference brain, provides a more comprehensive view of the spatial organization of DR serotonergic projections in the mouse. We did not find a prominent anterior-posterior topographic organization except that entorhinal cortex-projecting serotonin neurons tended to be localized to the posterior DR. We did observe a prominent division along the dorsal-ventral axis in the anterior DR, where ventral and dorsal serotonin neurons preferentially innervate cortical and subcortical targets, respectively, confirming and extending previous reports (Lowry et al, 2005;Muzerelle et al, 2016;Prouty et al, 2017). We further uncovered a strong correlation between cortical projections and Vglut3 co-expression in DR serotonin neurons.…”
Section: Anatomical Organization Of the Dr Serotonin Systemsupporting
confidence: 91%
“…Our retrograde tracing from eight diverse target sites, combined with image registration to compare the data in the same reference brain, provides a more comprehensive view of the spatial organization of DR serotonergic projections in the mouse. We did not find a prominent anterior-posterior topographic organization except that entorhinal cortex-projecting serotonin neurons tended to be localized to the posterior DR. We did observe a prominent division along the dorsal-ventral axis in the anterior DR, where ventral and dorsal serotonin neurons preferentially innervate cortical and subcortical targets, respectively, confirming and extending previous reports (Lowry et al, 2005;Muzerelle et al, 2016;Prouty et al, 2017). We further uncovered a strong correlation between cortical projections and Vglut3 co-expression in DR serotonin neurons.…”
Section: Anatomical Organization Of the Dr Serotonin Systemsupporting
confidence: 91%
“…The electrophysiological properties of the FG‐labeled neurons closely aligned with established properties characteristic of DR serotonergic neurons, including long AP duration and large amplitude AHP with slow recovery time (Calizo et al., ; Tuckwell, ; Vandermaelen & Aghajanian, ). Those signature electrophysiological features in conjunction with our previous neurochemical study showing that the vast majority of DR neurons projecting to mPFC or LGN were tryptophan hydroxylase‐positive (Prouty et al., ), provide strong support for the putative serotonergic identity of the recorded neurons.…”
Section: Discussionsupporting
confidence: 74%
“…Using the same rat strain, tracer, and stereotaxic procedures, we have previously shown that 90% of 2238 labeled DR‐mPFC neurons and 95% of 2117 DR‐LGN neurons (total counts from six animals per group) were positive for tryptophan hydroxylase, indicating that both structures receive strong, primarily serotonergic projections from the DR (Prouty et al., ). The distribution of labeled cells in the current experiments matched closely with our previous report.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Serotonin is secreted from afferent terminals originating from neurons in the dorsal and median raphe nuclei, which act on subcortical and cortical areas [3,4] to regulate various brain functions [5][6][7]. For example, serotonergic neurons regularly fire at low frequencies (0.2-4 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111…”
Section: Introductionmentioning
confidence: 99%